Composing Criteria of Individuation in Copredication. (20th August 2016) - Gotham, Matthew
Abstract: Copredication is the phenomenon whereby two or more predicates are applied to a single argument, but those predicates appear to require that their argument denote different things. This article focuses on the problem of individuation and counting in copredication: many quantified copredication sentences have truth conditions that cannot be accounted for given standard assumptions, because the predicates used impose distinct criteria of individuation on the objects to which they apply. I propose a compositional system for criteria of individuation and show that it improves predictions regarding the truth conditions of numerically quantified copredication sentences compared to existing accounts.